2020
DOI: 10.1042/bsr20192826
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin inhibited the proliferation and metastasis of androgen-independent prostate cancer cells by targeting the mitochondrion-dependent intrinsic apoptotic and PI3K/Akt/mTOR pathway

Abstract: The present study investigated the effects of Isorhamnetin on two types of prostate cancer cells (androgen-independent and androgen-dependent) and explored its possible mechanisms underlying such effects. Treatment with Isorhamnetin significantly inhibited cell growth and induced lactate dehydrogenase (LDH) release of androgen-independent DU145 and PC3 prostate cancer cells, but exhibited almost no toxicity effect on androgen-dependent LNCaP prostate cancer cell line or normal human prostate epithelial PrEC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Western blot assay was performed as previously reported [25] with slight modifications. After incubation, the MDSCs isolated from difference group were washed three times with ice-cold PBS and suspended in RIPA lysis buffer for total cell protein extraction.…”
Section: Western Blotmentioning
confidence: 99%
“…Western blot assay was performed as previously reported [25] with slight modifications. After incubation, the MDSCs isolated from difference group were washed three times with ice-cold PBS and suspended in RIPA lysis buffer for total cell protein extraction.…”
Section: Western Blotmentioning
confidence: 99%
“…Prostate cancer, as one most prevalent urinary malignancy of the male, ranked the second place in the cause of cancer death among aged men all over the world, trailing only lung cancer [ 1 , 2 ]. Although its incidence remains relatively high in western countries, there is a sharp rise in China for the aging Chinese population over the past decade, which has caught China’s healthcare attention [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isorhamnetin is a representative avonoid compound that exhibits antitumor activity primarily by inhibiting tumor cell proliferation, inducing apoptosis, and inhibiting signal transduction. For instance, Cai et al reported that isorhamnetin inhibits the proliferation and metastasis of androgen-independent prostate cancer cells by targeting the endogenous apoptotic pathway and selectively inhibiting PI3K/Akt/mTOR signaling [40].…”
Section: Discussionmentioning
confidence: 99%